Getting critical - Williams, Kate (Hampshire Palgrave Macmillan, 2009)
Students need to think critically about what they read or hear. This accessible guide shows students what being 'critical' in their work means, and how to bring that 'critical' dimension into all the work they do. It addresses the need and the skills of being critical in relation to reading and writing and is ideal for students at any level.